Team of Teams: New Rules of Engagement for a Complex World - McChrystal, General Stanley; Silverman, David; Collins, Tantum; Fussell, Chris (Portfolio Penguin, 2015)
As commander of Joint Special Operations Command (JSOC), General Stanl ey McChrystal discarded a century of management wisdom and pivoted fro m a pursuit of mechanical efficiency to organic adaptability. In this book, he shows how any organization can make the same transition to ac t like a team of teams - where small groups combine the freedom to exp eriment with a relentless drive to share their experience.Drawing on a wealth of evidence from his military career and sources as diverse as hospital emergency rooms and NASA's space program, McChrystal frames the existential challenge facing today's organizations, and presents a compelling, effective solution.